HEALTH AND SOCIAL ISSUES OF INFERTILE WOMEN IN PAKISTAN - Muhammad, Dildar; Begum, Nasim (Annals of Allied Health Sciences, 2019)
Infertility can be defined failure to conceive after regular sexual intercourse for one or two years in the absence of any known reproductive pathology(1). Infirtility bring with it social, legal and psychological complications. Couple with infirtility, especially the women partners are discriminated against and are stigmatized(2). Women are suffered in Pakistan same in as in other parts of South Asia due to failure to have a live birth. Stigmatization and blame of infertility lay on women only. Pakistani’s families demand children preferably male after marriage. Consequences of both primary and secondary infertility has occurred in the form of marital instability, divorce, emotional harassment, husband’s remarrying, and deprivation of inheritance or being sending to her parents’ home(3). Infertile women are often excluded from family celebrations, get punishment with physical violence, taunting and stigmatized. Many infertile women are punished with holding their food and remain deprived of their treatment in Pakistan. All these troubles result in psychological disturbance and lead them to insecurity, lack of self-confidence and self-esteem. Treatment procedures in Pakistan which are expensive and tiring process aggravate their problems(4). Compared to the country overall, people from KPK and adjoining FATA where Pathans are the majority ethnic group and socio-culture along-with religious opinions dictate personal and interpersonal life-decisions, being an infertile couple is dreadful(5). Infertility is not the product of incompetence on part of the female only, but men related issues are equally prevalent and important. Infertility should be considered more like a social problem than the mere medical problem, and ladies with infertility shall be given holistic care i.e. care for the patient and not merely the medical condition(6). Since fertility can be heavily influenced by the psychological satisfaction of the female partner in the couple, healthcare providers shall focus on the psychological well-being, mental relaxation and made in control of their situation. Fertility clinics shall have a psycho-social counselor, who should specifically focus on the negative thoughts of the infertile clients and address the hostile thoughts of the in-laws.